Das Management des (un)erwünschten Ressourcenüberschusses - Teil I. Funktionen, Zustände und Entstehung des organizational slack - Hans-Christian Krcal (University of Heidelberg, Department of Economics, 2009)
The object of the present analysis is organizational slack. The paper targets at a "slack type" which consists of basic information deriving from slack functions, slack conditions, antecedents of slack and dispositional requirements of slack. The purpose of the analysis is the creation of a preliminary heuristic for slack search, which combines all preconditions for systematical use of slack. The paper is the first part of an analysis series to the ambivalent role of organizational slack as an indicator of efficiency and inefficiency in the resource allocation process of a firm.
Keywords: D23; L29; M10; 330; organizational slack; antecedents; dispositional requirements; resources; Kapazitätsauslastung; Theorie